2019
DOI: 10.2134/jeq2018.07.0284
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Measurement of Nitrate Flux and Attenuation Using a Soil Passive Flux Meter

Abstract: This work enhances our understanding of catchment‐scale N budgets by demonstrating the modification and application of a simple method for direct in situ measurements of vadose zone nitrate leaching and attenuation. We developed a soil passive flux meter (SPFM) to measure solute leaching based on a modified design of ion‐exchange resin columns, and we tested the design in numerical simulations, laboratory experiments, plot‐scale field experiments, and a catchment‐scale field deployment. Our design minimized fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 59 publications
(76 reference statements)
1
8
0
Order By: Relevance
“…The SPFM results from Desormeaux et al (2019) suggest that turf systems are highly efficient at attenuating N inputs from urban fertilizer, which is in line with previous research reporting N attenuation of 80-100% across both fertilized (Trenholm & Sartain, 2010) and unfertilized (Herrmann & Cadenasso, 2017) turf systems. Our estimates of N attenuation in crop and pasture systems are close to the global average N use efficiency of 47% (Lassaletta et al, 2014) and agree with estimates for Florida production systems (Prasad & Hochmuth, 2016).…”
Section: Journal Of Geophysical Research: Biogeosciencessupporting
confidence: 90%
See 4 more Smart Citations
“…The SPFM results from Desormeaux et al (2019) suggest that turf systems are highly efficient at attenuating N inputs from urban fertilizer, which is in line with previous research reporting N attenuation of 80-100% across both fertilized (Trenholm & Sartain, 2010) and unfertilized (Herrmann & Cadenasso, 2017) turf systems. Our estimates of N attenuation in crop and pasture systems are close to the global average N use efficiency of 47% (Lassaletta et al, 2014) and agree with estimates for Florida production systems (Prasad & Hochmuth, 2016).…”
Section: Journal Of Geophysical Research: Biogeosciencessupporting
confidence: 90%
“…Natural attenuation in the soil represents the total attenuation from crop uptake and gaseous losses, and we used the same values for soil attenuation of manure N in livestock production systems and fertilizer N in crop production. Previous work has suggested that manure‐based systems result in greater N attenuation (Xia et al, ), and the absolute value of the average N recovery at the pasture sites was greater than crop sites (Desormeaux et al, ). Land management practices varied substantially within land use categories and exerted a strong control on net N inputs below the root zone; however, evaluating the influence of site‐specific land management practices at the catchment scale remains for future work.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations